Estimation of Different Values in Dasmula Tail - Saxena, R.B. (Asian Journal of Chemistry, 2010)
In the present investigation, the author has estimated the saturated andunsaturated acids, iodine, refractive index, bromide number and thiocyanogenvalues of Dasmula tail.